Imperforate Anus with Jejunal Atresia Complicated by Intestinal Volvulus: A Case Report - Hae Soo Joung; Alexandra Leon Guerrero; Sandra Tomita; Keith A. Kuenzler (EL-Med-Pub, 2020)
Anorectal malformations (ARMs) commonly co-occur with other congenital anomalies, particularly VACTERL (vertebral, anorectal, cardiac, tracheal, esophageal, renal, limb, and duodenal) associations. However, this collection of associations is not comprehensive, and other concurrent anomalies may exist that can be missed during the standard work-up of patients with ARMs. We present a rare case of a neonate with a low ARM with concurrent jejuno-ileal atresia that was diagnosed after the correction of the ARM when the patient developed segmental volvulus. This case illustrates the importance of having a high index of suspicion when deviation from a classic presentation occurs.